NSAID Induced Stevens Johnson Syndrome or Tumor Epidermal Necrolysis - Kumar, Meriga Pramod; Kumar, Tiruttani Sasi; Girirajsekhar, Dornadula (Journal of Pharmacy Practice and Community Medicine)
Non-steroidal Anti-inflammatory Drugs (NSAIDs) are the drugs which commonly prescribed and consumed by worldwide. NSAIDs are the several drugs which are having the high risk of inducing SJS or TEN. SJS or TEN are the cutaneous reactions involves in detachment of mucosal or skin membrane. Female were more affected than male. Major cause of SJS or TEN were the genetic (HLA –A and HLA- B), drugs, infection (mycoplasma pneumonia and herpes simplex virus). The exact pathogenic mechanism of SJS or TEN are uncertain. People who are having more than 40 years are the mostly affected by SJS or TEN. Due to the rarity of these diseases, sufficient evidence is still lacking to support the best choice of treatment for patients with SJS or TEN. Most of the drugs like antibiotics, anticonvulsant and NSAIDs which causes the SJS or TEN. Diagnostic test like skin prick test, PCR test, serology test was used to diagnose the SJS or TEN. Patients are treated with various drugs like immunomodulators (IVIG), Cyclosporine, systemic corticoSteroidals, TNF inhibitors, Plasmapheresis in addition to best supportive care.
Keywords: NSAIDs; Steven Johnson Syndrome; Tumor epidermal necrolysis; Drug reactions; Adverse reaction